Efficiency of the Free‐Radical Hydrophosphonylation of Alkenes: The Photoinduced Reaction of Dimethyl H‐Phosphonate with Enopyranoses as an Exemplary Case. Issue 24 (12th July 2013) - Dondoni, Alessandro; Staderini, Samuele; Marra, Alberto
Abstract: Free‐radical hydrophosphonylation of alkenes by H ‐phosphonates has been reported by other groups to occur under harsh conditions. On the other hand, we demonstrate in this paper that the hydrophosphonylation of alkene functionalized carbohydrates (enopyranoses) by dimethyl H ‐phosphonate can be carried out with high efficiency under neutral conditions at room temperature and with short reaction times using UV/Vis light irradiation in the presence of a suitable photoinitiator. Indeed, a range of structurally different allyl C ‐glycosides and exo ‐glycals were transformed into the corresponding glycosylalkyl phosphonates that were isolated in excellent yields (88–98 %), except for one case (45 %). A mechanism similar to that of the free‐radical photoinduced hydrothiolation of alkenes is proposed. Abstract : The photoinduced free‐radical addition of dimethyl H ‐phosphonate2 to allyl C ‐galactoside1a proceeds quickly at room temperature to give the corresponding sugar phosphonate3a in very high yield. The effectiveness and practicality of this metal‐free hydrophosphonylation reaction were validated by the coupling of2 with three more allyl C ‐glycosides as well as two exo ‐glycals.